2007
DOI: 10.1111/j.1540-8167.2007.00914.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pacing the Right Ventricular Mid‐Septum Tract in Patients with Permanent Atrial Fibrillation and Low Ejection Fraction

Abstract: The present study suggests that more physiological pacing from the RV sept can improve EF and quality of life (QoL) in patients with permanent AF and low EF needing a PM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 33 publications
3
28
1
1
Order By: Relevance
“…Furthermore, using this procedure, we achieved an extremely narrow pacing QRS width in lead II of the 12-lead electrocardiogram, as shown in this study. Compared to the QRS width for RV outflow tract pacing described in several reports, 20,21) the QRS width for RV mid-septal pacing was shown to be obviously narrower. Narrowing of QRS width suggests a reduction in the time for ventricular conduction and easier preservation of ventricular synchrony.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, using this procedure, we achieved an extremely narrow pacing QRS width in lead II of the 12-lead electrocardiogram, as shown in this study. Compared to the QRS width for RV outflow tract pacing described in several reports, 20,21) the QRS width for RV mid-septal pacing was shown to be obviously narrower. Narrowing of QRS width suggests a reduction in the time for ventricular conduction and easier preservation of ventricular synchrony.…”
Section: Discussionmentioning
confidence: 99%
“…In randomized studies, right ventricular nonoutflow septal pacing was compared with RVA pacing. According to LV echocardiographic parameters, the published results documented both the short-and long-term superiority of mid-septal pacing [14][15][16] . More definitive evidence of the potential benefits of pacing from various precisely defined septal sites over RVA is provided by the results of three randomized prospective multicenter studies -Optimize RV, Protect Pace, RASP -that are currently underway.…”
Section: Introductionmentioning
confidence: 98%
“…With Hisbundle pacing, a short paced QRS complex is recorded and interventricular dyssynchrony is not induced 21 . In earlier studies, the QRS duration was used as a criterion for selecting the optimal pacing site in the RV septum, with a confirmed hemodynamic benefit compared with RVA pacing 3,7,15 . Given this evidence and easy quantification of the parameter, paced QRS duration was selected as the only parameter of the optimal RV pacing site in this study.…”
Section: Justification Of Paced Qrs Duration As a Parameter Of The Opmentioning
confidence: 99%
“…A positive and statistically significant correlation was found between the paced QRS duration and global dyssynchrony (Victor et al, 2006;Flevari et al 2009;Takemoto et al, 2009;Muto et al, 2007). However, it has been shown in experimental studies that RV pacing sites maintaining an optimal LV function, are not correlated with the narrowest paced QRS complexes (Peschar et al, 2003).…”
Section: Electric and Mechanic LV Synchronymentioning
confidence: 86%
“…A pacing site that is in closer proximity with the proximal portion of His bundle at the RV septum should lead to a narrower QRS which in turn might reflect a lesser degree of activation delay compared with RVA pacing (Mera et al, 199;Schwaab et al, 1999;Tse et al, 2002) and less dyssynchrony, as demonstrated by multiple echocardiographic techniques (Tse et, 2002;Flevari et al, 2009;Takemoto et al, 2009;Gong et al, 2009;Leong et al, 2010;Cano et al, 2010). Pacing on the right ventricular (RV) septum, at high (septal RVOT pacing) (Giudici et al, 1997;Kolettis et al, 2000;Bourke et al, 2002;Tse et al, 2002;Dabrowska-Kugacka et al, 2009;Gong et al, 2009;Leong et al, 2010;Yoshikawa et al, 2010), mid (Yu et al, 2007;Cano et al, 2010;Muto et al, 2007) or lower (Flevari et al, 2009) septal pacing position has been introduced as a potentially favorable alternative to RVA pacing to preserve a more physiologic ventricular activation. Previous investigations of alternative pacing sites have yielded inconsistent results (Mera et al, 1999;Giudici et al, 1997;Bourke et al, 2002;Victor et al, 2006;Kypta et al, 2008;Dabrowska-Kugacka et al, 2009;Tse et al Europace 2009;Victor et al, 1999) which may be attributable, in part, to the fact that the pacing site was determined on a topological rather than functional basis (Giudici & Karpawich, 1999).…”
Section: Electric and Mechanic LV Synchronymentioning
confidence: 99%